ESTIMATED BLOOD LOSS IN CRANIOTOMY - Diana Sitohang; Rachmawati AM; Mansyur Arif (Faculty of Medicine, Hasanuddin University., 2016)
ABSTRACT Introduction: Estimated blood loss is an estimation of how much blood is loss during surgery. Surgical procedure requires a preparation of blood stock, but the demand for blood often larger than the actual blood used. This predicament happens because there is no blood requirement protocol being used. This study aims to determine the estimated blood loss during craniotomy procedure and it’s conformity to blood units ordered for craniotomy procedure. Methods: This study is a retrospective study using data from Wahidin Sudirohusodo General Hospitals’ medi- cal records in the period of January 2010-December 2012. We found 89 craniotomy patients that meet the inclusion criteria comprise of 66 men and 23 women. Results: This study showed that the average estimated blood loss in craniotomy was 3.20 units of whole blood (1120 ml) and the average of the demand of blood ordered was 4.0 units of whole blood (1400 ml). There was no mismatch between the amount of blood ordered for surgery and estimation of blood loss (p=0.73). Conclusion: Estimated blood loss in craniotomy procedure in Wahidin Sudirohusodo hospital, Makassar is 3.20 units of whole blood (1120 ml) was in accordance with amount of blood ordered for surgery. Keywords: Estimated blood loss, craniotomy